Special Issue “Advances in Monitoring Metabolic Activities of Microorganisms by Calorimetry” - Daumantas Matulis; Lars Wadsö; Karim Fahmy (Microorganisms, 2023)
In recent decades, the calorimetric monitoring of microbial metabolism, i [...]